Mutual regulation between butyrate and hypoxia‐inducible factor‐1α in epithelial cell promotes expression of tight junction proteins. (23rd March 2020) - Yin, Jiuheng; Zhou, Chao; Yang, Kunqiu; Ren, Yanbei; Qiu, Yuan; Xu, Pengyuan; Xiao, Weidong; Yang, Hua
Abstract: Inflammatory bowel disease is a kind of multi‐aetiological chronic disease that is driven by multidimensional factors. Hypoxia‐inducible factor‐1α (HIF‐1α) plays an important role in anti‐inflammatory and cellular responses to hypoxia. Previous studies have found that B or T‐cell‐specific HIF‐1α knock out mice exhibit severe colonic inflammation. However, we know very little about other functions of HIF‐1α in intestinal epithelial cells (IECs). In our study, HIF‐1α ΔIEC mice were used to study the function of HIF‐1α in IECs. HIF‐1α was knocked down in Caco‐2 cells by transfection with a small interfering (si) RNA. Immunohistochemical staining and western blotting were used to detect the expression of zonula occluden‐1 (ZO‐1) and Occludin. The content of colon was harvested for high‐performance liquid chromatography analysis to examine the levels of butyrate in the gut. Our research found that HIF‐1α played a protective role in dextran sulphate sodium‐induced colitis, which was partly due to its regulation of tight junction (TJ) protein expression. Further study revealed that HIF‐1α mediated TJ proteins levels by moderating the content of butyrate. Moreover, we found that butyrate regulated TJ protein expression, which is dependent on HIF‐1α. These results indicated that there is a mutual regulatory mechanism between butyrate and HIF‐1α, which has an important role in the maintenance of barrier function of the gastrointestinal tract.